Phenomenon-model-based AM-FM vibration mechanism of faulty spur gear. (1st December 2019) - Yang, Xiaoqing; Ding, Kang; He, Guolin
Highlights: Meshing stiffness with FM is deduced considering the actual speed fluctuation. AM-FM sideband features are analyzed based on phenomenon-models of gear pair. The mathematic modulation models of vibration responses are built. Derived results based on phenomenon-models are verified by experimental tests. Abstract: Vibration responses of faulty gear contain modulation components that are commonly used as the indicators to detect the fault. The modulation mechanism has not been revealed clearly, especially the sideband distribution of amplitude modulation and frequency modulation. Aiming at the vibration modulation mechanism of fault gear, the gear meshing stiffness with frequency modulation components is deduced considering the actual speed fluctuation, as well as its influence on vibration responses. A series of phenomenon models of gear pair are built to research the sideband distribution features of vibration responses related to different types of gear faults. Both the steady-type and impact-type gear faults are proved to generate asymmetric amplitude-frequency modulation sidebands around harmonics of the meshing frequency. The marked difference lies in that the steady-type fault features distribute within a finite band while the impact-type fault features cover the entire frequency range and induce spurious resonance peaks. Sidebands with both amplitude and frequency modulations are wider than those with only amplitude modulation, and the product of two groups of frequency modulation components is proved to bring in amplitude modulation components. The phenomenon models of gear vibration responses contribute a deeper understanding of modulation mechanism of faulty spur gear, and the obtained sideband distribution features of amplitude-frequency modulation are an effective aid for gear fault diagnose.